An Analysis of Aligning Supply Chain Management With Business Strategy - Anny Nurbasari; M. Saputra; Paisal Halim; Viola De Yusa; Ramlan Siregar; Besti Lilyana; I Wayan Suparta (International Journal of Supply Chain Management, 2020)
Abstract- The main objective in this research is attempting to demonstrate alignement mechanism of supply and bussiness strategy. Companies are beginning to view supply chain management and procurement as a rising priority. Procurement has traditionally been a cost-driven model, finding suppliers that can provide the best product at the lowest cost. In stressing the sociotechnical qualities of the supply chain, it is argued the bussiness is the only common element to the entire demand chain. Brand strategy management should be both a demand and supply chain priority, in contrast to its general demand chain focus. It is restrictive lawful rights that secure works of initiation, structure or work of art. A business strategy of any work save the distribution, creation or clearance of the rights to education, melodic, imaginative work, sensational, computer program, or to utilization of a business print or mark. Results showed that having a strong brand not only supports your interactions with stakeholders but with your employees and suppliers too. This is especially important if you are driving transformation within the organization.